Negative beliefs about the self prospectively predict eating disorder severity among undergraduate women. (April 2020) - Williams, Brenna M.; Levinson, Cheri A.
Abstract: Social anxiety disorder (SAD) and eating disorders (EDs) are highly comorbid. Negative self-portrayal, or 'perceived flaws in the self, ' is a key feature of SAD and consists of three self-critical aspects that are presumed to be flawed: social competence, physical appearance, and signs of anxiety. Negative self-portrayal has yet to be studied among EDs, despite research suggesting that individuals with EDs have a greater negative self-image and self-criticism. The identification of negative self-portrayal as a shared risk factor for SAD and EDs may have important implications for both prevention and treatment. The current study ( N  = 300 undergraduate women) aimed to extend negative self-portrayal theory to the EDs. We found that several aspects of negative self-portrayal were related to ED severity and that physical appearance concerns predicted subsequent ED severity. In a cross-sectional model of shared vulnerability, we found that physical appearance concerns were a shared correlate of SAD and ED symptoms. In a prospective shared vulnerability model, we found that (a) physical appearance prospectively predicted ED severity and (b) symptoms of SAD prospectively predicted all aspects of negative self-portrayal. Concerns about flaws in appearance should be targeted in the treatment of EDs, as this aspect of negative self-portrayal was shown to predict subsequent ED severity. Future research should further investigate the theory of negative self-portrayal as it pertains to EDs. Highlights: Negative beliefs about the self are related to eating disorder severity. Social anxiety disorder symptoms predicted negative beliefs about the self. Negative beliefs about one's physical appearance predicted eating disorder severity.